˙OH-initiated heterogeneous oxidation of methyl orange using an Fe–Ce/MCM-41 catalyst. Issue 23 (15th February 2016) - Wang, Shuaijun; Zhao, Chaocheng; Wang, Dejun; Wang, Yongqiang; Liu, Fang
Abstract : Surface-bound ˙OH radicals play a dominant role in the oxidation of methyl orange. Abstract : In this study, a simple and active Fe3 O4 –Fe2 O3 –CeO2 /MCM-41 (Fe–Ce/MCM-41) catalyst was fabricated, using iron and cerium species that were simultaneously immobilized on a MCM-41 zeolite surface, and employed as a heterogeneous Fenton-like catalyst for the oxidation of methyl orange (MO) for the first time. The activity of the Fe–Ce/MCM-41 catalyst was evaluated based on the degradation of MO, and the effects of the operating conditions ( i.e., pH value, catalyst addition, hydrogen peroxide (H2 O2 ) concentration and MO concentration) on degradation performance were investigated. The kinetics results indicated that MO removal followed pseudo-first order kinetics. Based on the analysis of metal leaching, X-ray photoelectron spectroscopy, and the effects of radical scavengers, MO in the bulk solution was primarily oxidized by surface-bound ˙OH, which was generated by the reaction of Fe 2+ and Ce 3+ species with H2 O2 on the catalyst surface. The as-prepared Fe–Ce/MCM-41 catalyst exhibited excellent performance without the aid of ultrasonic and UV light irradiation, which can decrease the operating costs. In addition, this process may be promising for application in practical wastewater treatment.